Penerapan Electronic Medical Record di Rumah Sakit: Sebuah Model Untuk Memahami Penerimaan Dokter Atas Teknologi Baru - Kadek Dwi Cahyawan; Luh Putu Mahyuni (Jurnal Manajemen dan Bisnis, 2022)
This study aims at exploring factors that explain specialist doctors’ acceptance of a new technology adoption, particularly electronic medical record (EMR) adoption, which is still relatively low in Indonesia. Qualitative approach through interviews with specialist doctors was conducted to answer research questions. Technology Acceptance Model (TAM) dan Theory of Planned Behavior (TPB) were applied as guiding theories. Data were analyzed by using coding and theming method. This study suggests a comprehensive model that explains factors determining the acceptance of a new technology, particularly EMR. This model consists of two major explanatory variables, namely: perceived usefulness and perceived ease of use. The two major explanatory variables are explained by three factors, namely: 1. External factor influences (image, training, and managerial support); 2. Cognitive instrumental process (computer anxiety, computer self-efficacy, and computer playfulness); 3. Perceived barriers (system integration and internet network/connection). Findings of this study could be used as a valuable reference by hospital managers to better understand factors that could influence the success of a new technology adoption. Even though this study was conducted in hospital context, the model offered might also be applied in other industries context that have plan to implement a new technology.